KATA PENYUKAT DALAM AKTIVITAS PERTANIAN MASYARAKAT DESA SEBAWI KECAMATAN SEBAWI KABUPATEN SAMBAS - Diarty, Eny; Sulissusiawan, Ahadi; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to find out objectively about the forms, categories, meanings, and functions of the word measure in Sambas Malay and how the form of the e-module about the word measure is for learning at school. This research uses a descriptive method with a qualitative form data collection techniques in this study are using observation techniques, interview techniques, recording techniques, and notetaking techniques. This research produced 41 data, 38 data classified into single form and 3 data classified into complex form. The 41 data based on the research were divided into 3 categories, namely the verb category with 2 data, the noun category with 37 data, and the numerals category with 2 data. The meaning contained in the word measure in agricultural activities using Sambas Malay is based on lexical meaning. The 41 data were analyzed for the function/usefulness of each of the interrogative words. The form of e-modules in the agricultural activities of the Sebawi village community can be used as teaching materials for Indonesian language learning teachers in the form of descriptive text.